Bilateral breast cancer following augmentation mammaplasty with polyacrylamide hydrogel injection: A case report - ZHAO, YANING (Oncol Lett, 2015)
Breast cancer occurring following injection with polyacrylamide hydrogel (PAMG) for augmentation mammaplasty is rare. The present study reports the case of a 43-year-old female presenting with bilateral breast cancer 10 years after augmentation mammaplasty with PAMG injection and no family history of breast cancer. A 5.5×6.0-cm mass in the right breast with multiple intumescent axillary lymph nodes was revealed and a palpable mass of ~1.0 cm was identified in the outer upper quadrant of the left breast. Multiple smaller nodules were observed in the pulmonary field. Pathological examination revealed invasive lobular grade II carcinoma in both breasts with ER(+++), PR(+++), C-erbB2(−), Top-2(+), in the right breast and ER(++), PR(++), c-erb-B2(−), Top-2(+) in the left. Preoperative chemotherapy, modified radical bilateral mastectomy with axillary clearance, postoperative chemotherapy, and an oophorectomy were conducted, followed by treatment with Arimedex® until the present date A number of valuable insights can be garnered from this case. First, close follow-up is required for female patients who receive an injection of PAMG for augmentation mammaplasty in order to achieve an early diagnosis and to intervene in any incidences of breast cancer. Second, the differential diagnosis of dual primary carcinoma versus metastatic breast cancer is important and may be aided by the use of molecular technology. Third, it remains difficult to determine gene expression values for the prediction of chemotherapy sensitivity. Thus, discrimination between primary and secondary carcinomas is the principle barrier for identifying an appropriate treatment strategy when a patient is diagnosed with bilateral breast cancer.